2011
DOI: 10.1186/1743-7075-8-55
|View full text |Cite
|
Sign up to set email alerts
|

Dietary long-chain, but not medium-chain, triglycerides impair exercise performance and uncouple cardiac mitochondria in rats

Abstract: Short-term consumption of a high-fat diet impairs exercise capacity in both rats and humans, and increases expression of the mitochondrial uncoupling protein, UCP3, in rodent cardiac and skeletal muscle via activation of the transcription factor, peroxisome proliferator-activated receptor α (PPARα). Unlike long-chain fatty acids however, medium-chain fatty acids do not activate PPARα and do not increase muscle UCP3 expression. We therefore investigated exercise performance and cardiac mitochondrial function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Performance was elevated both above baseline running performance and above that of rats that were pair fed isocaloric diets with ketone ester replaced with fat or carbohydrate. In previous studies, using this protocol, we have found that provision of a high‐fat diet (55% of kcal from fat) worsened running performance in rats (15), as did a diet in which long‐chain triglycerides (46% kcal) were provided, although rats that consumed medium‐chain triglycerides (46% kcal; associated with increased ketone body production) were not affected to the same extent (42). Researchers have proposed the use of the ketogenic diet as a training aid because of its effects in elevating muscle fatty acid oxidation rates (43).…”
Section: Discussionmentioning
confidence: 90%
“…Performance was elevated both above baseline running performance and above that of rats that were pair fed isocaloric diets with ketone ester replaced with fat or carbohydrate. In previous studies, using this protocol, we have found that provision of a high‐fat diet (55% of kcal from fat) worsened running performance in rats (15), as did a diet in which long‐chain triglycerides (46% kcal) were provided, although rats that consumed medium‐chain triglycerides (46% kcal; associated with increased ketone body production) were not affected to the same extent (42). Researchers have proposed the use of the ketogenic diet as a training aid because of its effects in elevating muscle fatty acid oxidation rates (43).…”
Section: Discussionmentioning
confidence: 90%
“…In regard to the role that FAs might have on both UCP2 and UCP3 regulation, it has to be noted that oleic acid has been suggested to stimulate the activity of the promoter regions of UCP2 and UCP3 genes and the FA responsive regions . Another study has reported that medium‐chain fatty acids, such as lauric acid contained in SOLF, are less efficient that long‐chain fatty acids in triggering cardiac mitochondrial uncoupling; therefore, the difference between SOLF and UOLF adolescent mice could be due in part to the elevated lauric acid content in in SOLF.…”
Section: Discussionmentioning
confidence: 99%
“…The putative KD utilized in the current study contained fat sources primarily from medium chain triglycerides (i.e., MCTs, canola oil, and flaxseed oil). Interestingly, it has been reported that long-chain triglycerides, but not medium-chain triglycerides, can result in uncoupling of mitochondrial respiration along with increased uncoupling protein expression (Murray et al, 2011). This observation would explain the increased uncoupling protein expression and respiration rates described in previous studies, while our current findings may be explained by long-chain triglycerides in the WD-fed animals causing an uncoupling stimulus in complex II and lack of this stimulus in KD-fed animals.…”
Section: Discussionmentioning
confidence: 99%